2017
DOI: 10.3917/rne.094.0219
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory in amnesia

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…It could be hypothesized that the symptoms of our patient were similar to those observed in confabulation. Among the four forms of confabulation (Schnider, Nahum, & Ptak, 2017), patients with behaviorally spontaneous confabulation are disoriented in context and time, with memories recalling real events and activities in the patient's past but in the wrong temporal context (Kopelman & Marsh, 2017), which is quite similar to the "transposition in the past" phenomenon observed in our patient. However, in our case, the phenomenon was probably not associated with confabulation for several reasons.…”
Section: Discussionsupporting
confidence: 67%
“…It could be hypothesized that the symptoms of our patient were similar to those observed in confabulation. Among the four forms of confabulation (Schnider, Nahum, & Ptak, 2017), patients with behaviorally spontaneous confabulation are disoriented in context and time, with memories recalling real events and activities in the patient's past but in the wrong temporal context (Kopelman & Marsh, 2017), which is quite similar to the "transposition in the past" phenomenon observed in our patient. However, in our case, the phenomenon was probably not associated with confabulation for several reasons.…”
Section: Discussionsupporting
confidence: 67%
“…Like others before them (Winocur et al, 2009;Lehmann, Lacanilao & Sutherland, 2007;,reviewed in Sutherland & Lehmann, 2020;Sekeres et al, 2018a), they found that the extent of remote memory loss was not directly related the volume of the HPC. Instead, they found that it was mediated almost wholly by the correlated volume loss in the thalamus (see also Kopelman, 1999;Kopelman & Marsh, 2018), a point to which we will return later in the paper.…”
Section: William Et Al's Findings Temper the Conclusion Drawn By Mccormick Et Al And Suggest Thatmentioning
confidence: 97%
“…Because a major distinction between SCT and MTT concerned differences in the fate of episodic and semantic memory, new psychological tests were devised that were sensitive to those differences (Kopelman et al, 1989;Kopelman & Marsh, 2018;Levine et al, 2002;Piolino et al, 2003Piolino et al, , 2009Renoult et al, 2020) enabling investigators to track them over time. To track memories over long time intervals, investigators examined autobiographical memory and memory for public events and personalities, and distinguished between episodic and semantic contributions to them (Moscovitch et al, 2005(Moscovitch et al, , 2006Sekeres et al, 2016Sekeres et al, , 2018Squire et al, 2015;Kopelman, 2019).…”
Section: Multiple Trace Theorymentioning
confidence: 99%